2016
DOI: 10.1007/s10461-016-1435-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic Resources and HIV Preventive Behaviors Among School-Enrolled Young Women in Rural South Africa (HPTN 068)

Abstract: Individual economic resources may have greater influence on school-enrolled young women's sexual decision-making than household wealth measures. However, few studies have investigated the effects of personal income, employment, and other financial assets on young women's sexual behaviors. Using baseline data from the HIV Prevention Trials Network (HPTN) 068 study, we examined the association of ever having sex and adopting sexually-protective practices with individual-level economic resources among school-enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
9
0
1
Order By: Relevance
“…The findings demonstrate that not only does the hybrid microfinance/productive assets loan program provide economic empowerment for the young adolescent and family, but also improves adolescent health and school attendance in a rural humanitarian setting. This finding is consistent with other evidence that demonstrated benefits beyond economics with asset-based economic interventions such as improved psychosocial outcomes [26,27]. Tangible assets, such as the rabbit and offspring, can influence the adolescent's future outlook and reduce risk behaviors such as leaving school early to work in the local mines.…”
Section: Discussionsupporting
confidence: 89%
“…The findings demonstrate that not only does the hybrid microfinance/productive assets loan program provide economic empowerment for the young adolescent and family, but also improves adolescent health and school attendance in a rural humanitarian setting. This finding is consistent with other evidence that demonstrated benefits beyond economics with asset-based economic interventions such as improved psychosocial outcomes [26,27]. Tangible assets, such as the rabbit and offspring, can influence the adolescent's future outlook and reduce risk behaviors such as leaving school early to work in the local mines.…”
Section: Discussionsupporting
confidence: 89%
“…The Swa Koteka intervention provided cash payments to both girls and their guardians, conditional on school attendance, and also provided testing and counseling components once a year when girls underwent HIV/HSV-2 testing. Behind this intervention design was the theory that schooling was protective for HIV risk, but also that women’s economic security and empowerment are strongly interconnected, a link that was demonstrated at baseline among young women enrolled in this study (Jennings et al 2017 ). In particular, Jennings et al ( 2017 ) showed that among sexually active young women, having greater economic resources in the form of individual-level resources, like savings and spending money, was associated with safer sexual behaviors (Jennings et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there was no effect of the CCT intervention on HIV incidence, there were some improved sexual behaviors and a large reduction in the risk of intimate partner violence [39]. An analysis of baseline data also showed that individual economic resources among the study sample were associated with a number of HIV preventive practices including periodic sexual abstinence, having fewer sexual partners, and consistent condom use [31]. Further, a qualitative analysis by MacPhail et al (2017), found young women in the treatment group experienced a number of benefits due to the cash itself, including enhanced status with peers and feelings of independence, which may have consequently affected their sexual risk-taking behavior and psychosocial well-being [40].…”
Section: Introductionmentioning
confidence: 92%
“…One recent study found more positive associations between individual economic resources and protective sexual behaviors among sexually active young women in South Africa [31] while others have been more mixed [29,30]. In Cameroon, women (aged with greater economic resources displayed more protective factors such as greater HIV knowledge and more condom use but were also more likely to test positive for HIV and to engage in riskier sexual behaviors such as having multiple partners in the past 12 months [30].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation